1996
DOI: 10.1161/01.hyp.27.6.1210
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hypertension with β 2 - and α 2c10 -Adrenergic Receptor Genotype

Abstract: The adrenergic receptors have been implicated in the pathogenesis of essential hypertension. We hypothesized that hypertension is associated with variants at the beta2-adrenergic receptor locus and at one of the alpha2-adrenergic receptor loci. In unrelated individuals, we measured untreated blood pressure and characterized each subject as hypertensive or normotensive. We then used genomic DNA to identify beta2- and alpha2c10-adrenergic receptor restriction fragment length polymorphisms. In 175 subjects (49 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…Genotyping using the restriction enzyme DraI, which allows the detection of polymorphism in the 3V-flanking region of the a2A-AR gene, generated inconsistent results. Indeed, association between this polymorphism and hypertension was found in a white population in one study [40] but not in another [50]. On the other hand, a third report has demonstrated the presence of association in black American population [38].…”
Section: Physiological Consequences and Clinical Associations Of The mentioning
confidence: 87%
“…Genotyping using the restriction enzyme DraI, which allows the detection of polymorphism in the 3V-flanking region of the a2A-AR gene, generated inconsistent results. Indeed, association between this polymorphism and hypertension was found in a white population in one study [40] but not in another [50]. On the other hand, a third report has demonstrated the presence of association in black American population [38].…”
Section: Physiological Consequences and Clinical Associations Of The mentioning
confidence: 87%
“…The most frequently studied is the DraI RFLP in the context of hypertension and related phenotypes. An initial report showed a marginal (P ϭ 0.03) association between the DraI RFLP and hypertension in Caucasians but not African Americans (11). In contrast, another study revealed a marginal (P ϭ 0.02) association with this RFLP and hypertension in African Americans but not Caucasians (12).…”
Section: Variation Of the ␣2aar Gene Alters Transcript And Protein Exmentioning
confidence: 99%
“…The critical roles of ␣ 2A ARs in these physiologic processes has prompted association and family studies of receptor genetic variability to identify potential risk factors or disease modifiers and pharmacogenomic studies to identify potential treatment-response loci for multiple central nervous system, cardiovascular, and metabolic diseases (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). These studies were performed with single restriction fragment-length polymorphisms (RFLPs) of the ␣ 2A AR gene, such as a DraI RFLP, and generally have shown only weak or no associations or a lack of reproducibility.…”
mentioning
confidence: 99%
“…For most of the noncoding polymorphisms, no associations have been found with multiple pathological conditions linked to α 2A AR function, including hypertension, panic and mood disorders, schizophrenia, and obesity (92,99,(101)(102)(103)(104)(105). In contrast, several clinical phenotypes, including hypertension, body fat distribution, and glucose metabolism, have been shown to be associated with a Dra I restriction fragment length polymorphism within the 3 UTR (106)(107)(108)(109). However, because the functional relevance of this polymorphism has not been determined, the significance of these results remains unclear.…”
Section: Human Studiesmentioning
confidence: 99%